2007
DOI: 10.1177/0731684407083005
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Analysis of Simply Supported Beams

Abstract: In this study, two deflection functions due to flexure and shear have been obtained for the global form of composite materials. Two different composite materials are selected for comparison of these deflection functions. These composites are: polymer matrix composite simply supported beam, reinforced by unidirectional fibers; and thermoplastic simply supported beam, reinforced by woven Cr-Ni steel fibers. In accordance with these different material properties, analytical and numerical solutions have been carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Also, investigations of the effect of shear on the deflection in simply supported composite beams have been recently carried out. [13][14][15] In a general review of material evaluation bending tests, Mullin and Knoell 16 discussed the theoretical origins of L t ratios (where L is the span length and t is the nominal thickness) and the effects of material variables and specimen defects such as voids. Westwater 17 observed that specimens with small L t ratios often fail by cracks running out to, or past, the support nose and also that the amount of overhang may affect the mode of failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, investigations of the effect of shear on the deflection in simply supported composite beams have been recently carried out. [13][14][15] In a general review of material evaluation bending tests, Mullin and Knoell 16 discussed the theoretical origins of L t ratios (where L is the span length and t is the nominal thickness) and the effects of material variables and specimen defects such as voids. Westwater 17 observed that specimens with small L t ratios often fail by cracks running out to, or past, the support nose and also that the amount of overhang may affect the mode of failure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, investigations of the effect of shear on the deflection in simply supported composite beams have been recently carried out. 1315…”
Section: Introductionmentioning
confidence: 99%